Green investments and firm performance - Iulia Siedschlag; Weijie Yan (The Economic and Social Research Institute (ESRI), 2020)
This paper examines the impact of firms' green investments on a range of performance outcomes including the growth of output, employment, productivity, export intensity, and energy intensity. The analysis uses firm-level data from Ireland's industry sector over the period 2008-2016. To identify causal effects, a difference-in-difference propensity score matching is implemented. In addition to average effects across all firms, we identify and quantify heterogenous effects for different groups of firms. Our results indicate that in the medium-term green investments have positive and statistically significant effects on firms' performance. Taking into account firm heterogeneity, we find that the effects are stronger for firms which are larger, foreign-owned, more productive, and in low-tech industries. Taken together, this evidence suggests that environmental quality and firm performance go together.
Keywords: D24; L25; Q50; Q58; 330; Environmental policy; green investments; firm performance